Conceptualising Coping and Resilience in the Context of Socio-Political and Economic Change: Generational Perspectives From Slovenia. Issue 4 (1st October 2020) - Kovačič, Tanja; Dolan, Pat
ABSTRACT: The significance of a wider social context in building youth resilience has recently been recognised, with the suggestion that resilience research requires a move from individual-level experience to wider social practices, discourses, and ideological positions. Relatively little research looks at rapid ideological change in state institutions and structures, or the consequent implications this has for understanding protective mechanisms and coping strategies among young people. Based on the socio-ecological approach to resilience, this article explores the meaning of youth resilience in the context of a sudden socio-political transformation in Slovenia. For this purpose, experiences with transitions to adulthood in 20 people growing up under socialism and post-socialism are compared. Narrative thematic analysis of the interviews shows two types of transitions to adulthood emerging: supported, and individualised This article shows that the meaning of youth resilience changes through socio-political and economic transformation. It emphasises the role that social policies and state ideologies have in shaping social ecologies and consequently youth perceptions of risk and coping: from social processes under socialism to an individual process in post-socialism.